Smartphone Based Fall Prevention Exercises - Bruno Filipe Neves Ferreira (2013)
Falls are one of the greatest problems facing ageing and older persons. Due to age-related changes and frailty, individuals may unintentionally lose balance or stability while performing activities of daily living, even without any external cause. Exercise programs focusing on muscle strengthening and balance retraining can be effective as part of a fall prevention approach in both community and residential aged care settings. This thesis is focused on the adaptation of effective fall prevention exercises/programs into a smartphone. The smartphone must guide the older persons throughout the exercises as well as advice about the desired frequency/duration of exercises and, when possible, evaluate the movement being performed (i.e. by using e.g. the accelerometer and gyroscope). So that older persons can make the exercises safely and easily on their own, as well as receive feedback about their movements' performance.